1983
DOI: 10.1139/v83-085
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of free base cocaine, C17H21NO4

Abstract: . Can. J. Chem. 61, 481 (1983).The crystal structure of free base cocaine has been determined in order to compare the conformation with that observed in its salts, and to clarify the powder pattern of the pure compound. Crystals of (-)-cocaine are monoclinic, space group P 2 , , a = 10.130(1), b = 9.866(2), c = 8.445(1) A, P = 106.92(1)", Z = 2, D, = 1.25 g cm-j. Data were collected with MoK, radiation on a modified Picker diffractometer using the NRCC diffractomcter control system. The structure was solved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…The calculations predict that the piperidine ring of cocaine adopts a chair conformation with the N-methyl group being equatorial. These features as well as the predicted bond lengths and bond angles were in reasonable agreement with those found for the solid free base by X-ray diffraction [22] and from an NMR and molecular mechanics study [23]. They were also in accord with a recent AM^ study of the conformations of cocaine and its diastereomers [24].…”
Section: Resultssupporting
confidence: 87%
“…The calculations predict that the piperidine ring of cocaine adopts a chair conformation with the N-methyl group being equatorial. These features as well as the predicted bond lengths and bond angles were in reasonable agreement with those found for the solid free base by X-ray diffraction [22] and from an NMR and molecular mechanics study [23]. They were also in accord with a recent AM^ study of the conformations of cocaine and its diastereomers [24].…”
Section: Resultssupporting
confidence: 87%
“…The reference crystal structure of cocaine, (CSD entry code: COCAIN10) (Scheme 1-I), was previously determined by single crystal X-ray diffraction (XRD) 39 at room temperature. The structure is comprised of 2 symmetry equivalent molecules in the unit cell, and it belongs to the P2 1 monoclinic space group with unit cell dimensions: a = 10.130(1) Å, b = 9.866(2) Å, c = 8.445(1) Å. Powdered flutamide (2-methyl-N(4-nitro-3-(trifluoromethyl)phenyl)propamide) was purchased from Sigma-Aldrich and used without further purification.…”
Section: Experimental 2a Samplesmentioning
confidence: 99%
“…Crystal structures indicated that the N-methyl in tropinone [27] and N-phenyl in the granatanone derivative [28] display the axial configuration in the solid state. The N-methyl configuration in the crystals depended on the derivative and was determined to be equatorial in cocaine [29] and its salts [30] as well as in phenyltropane [31], tropinone aldols [32,33], tropinone aldol tosylhydrazone [21], and granatanone aldols [34], but axial in scopolamine [35]. In some conformational studies of granatane derivatives by NMR methods [36], the N-methyl stereochemistry remained undetermined.…”
Section: Introductionmentioning
confidence: 99%